Penegakan Hukum Melalui Penerapan Restorative Justice dalam Sistem Peradilan Anak di Indonesia - Muldri Pudamo James Pasaribu; Putri Esta Napitu (Universitas Mataram, 2022)
Restorative justice which is the implementation of the concept of diversion has been formulated in the juvenile justice system, but a good system must be accompanied by an attitude which is imbued with the will to perceive and believe that this world is always getting better. Children are the nation's next generation and therefore their existence mustabe protected by the state. Itais also necessary legal infrastructure to anticipate any problems that arise. Departing from the above thought, it is related to the writing in this paper that will discuss about the application of restorativeajustice in the juvenile justice system in Indonesia. The results of this normative juridical study show that Restorative justice is the goal of implementing diversion to resolve child criminal cases in Indonesia.